2014
DOI: 10.1111/trf.12809
|View full text |Cite
|
Sign up to set email alerts
|

Predonation screening of candidate donors and prevention of window period donations

Abstract: Predonation screening of candidate donors very likely causes a loss of donations, but it might prevent undetected window period donations. Further studies are necessary to determine the value of predonation screening as an additional safety measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Our analysis of HIV WP‐NAT–yield rate in the same International NAT Study Group database documented a statistically significant 3.8‐fold higher incidence or risk in FT compared to lapsed plus repeat donations in South Africa, but no difference in the other regions . Despite data indicating increased risk of FT relative to repeat donations in some countries, given residual HCV transmission risks of approximately one in 10 million donations when performing ID‐NAT, we do not believe that predonation screening of FT donors (as currently practiced in some European countries) would provide significant incremental safety or be cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of HIV WP‐NAT–yield rate in the same International NAT Study Group database documented a statistically significant 3.8‐fold higher incidence or risk in FT compared to lapsed plus repeat donations in South Africa, but no difference in the other regions . Despite data indicating increased risk of FT relative to repeat donations in some countries, given residual HCV transmission risks of approximately one in 10 million donations when performing ID‐NAT, we do not believe that predonation screening of FT donors (as currently practiced in some European countries) would provide significant incremental safety or be cost‐effective.…”
Section: Discussionmentioning
confidence: 99%
“…A further study of undisclosed risk behavior in HIV-positive donors in Italy revealed heterosexual risk contacts in 68.1% [9]. Another retrospective analysis of pre-donation screening revealed acute HBV infections in donors reporting new heterosexual partners [11]. Also in the UK, there were more reported heterosexual exposures among infected blood donors (both with and without a partner with an identifiable risk) in 2014 than in the previous year, while other reported exposure like sex between men decreased [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, new donors undergo predonation testing, but at this first visit no blood is collected for transfusion purposes. 10 Repeat donors are donors who have donated for transfusion purposes before or first-time donors who proved eligible for donation based on predonation screening (at least 2 weeks prior). All TTI-positive repeat donors went from a documented negative to a positive donation; confirmed HCV-positive donors whose preceding donation was from before the introduction of anti-HCV screening in 1992 were categorized as new donors.…”
Section: Study Populationmentioning
confidence: 99%